Spaces of solidarity under constraints: The promotion of volunteering in the management of luggage storage for homeless people in Paris - Louka Herse (EchoGéo)
Based on the results of a two-year ethnographic study, the article analyses the voluntary work policy implemented by the City of Paris to set up luggage repositories for homeless people. Solidarity luggage storage are new forms of assistance that enable homeless people to keep their personal belongings safe. In Paris, which hosts most France's storage spaces for personal belongings, the creation and management of these centres is based on a municipal policy of mobilising volunteers. The City of Paris encourages and supervises free work by residents. As a result, the assistance network for homeless people is better equipped. However, the partnership between the municipality and voluntary associations raises a series of questions about the nature and quality of the municipal service provided, as it is akin to a form of non-profit privatisation of local public action.